On distributed symbolic control of interconnected systems under persistency specifications - Apaza-Perez, W. Alejandro; Combastel, Christophe; Zolghadri, Ali (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an abstraction-based technique to solve the problem of distributed controller design enforcing persistency specifications for interconnected systems. For each subsystem, controller synthesis is based on local distributed sensor information from other subsystems. An effective method is presented for quantification of such partial information in an abstraction in terms of level sets of Lyapunov-like ranking functions. The results are illustrated on a laboratory hydraulic system.
Keywords: symbolic controller synthesis; distributed controller; interconnected systems